Pemanfaatan E-Learning Sebagai Adaptasi Pembelajaran New Normal - Uun Ahmad Saehu; Henny Zurika Lubis; Pipit Putri Hariani MD (EDUTECH, 2022)
This research was conducted to determine the use of e-learning as an adaptation of new normal learning. descriptive qualitative as data analysis with data collection techniques in the form of literature studies, documentation and questionnaires. From the test, through e-learning used properly because by utilizing e-learning it can provide convenience for students and lecturers. Students can easily study anytime anywhere without fear of missing out on the material because they are able to manage and store existing files. From the lecturer's point of view, they are not always the benchmark of learning resources so they have the opportunity to challenge themselves to learn, learning is achieved and lecturers become innovative in improving the presentation of material there and to students